FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN PEMBAYARAN DIVIDEN PADA PERUSAHAAN NON-KEUANGAN - ANUGRAWATY ANUGRAWATY; SUGIARTO PRAJITNO (Jurnal Bisnis dan Akuntansi, 2017)
The purpose of this research is to provide empirical evidence whether firm maturity, profitability, investment opportunities, leverage, firm size, liquidity, previous year’s dividend and free cash flow have an influence to dividend policy. This study is also to improve consistency of results from prior researchers. Population of this research is non-financial companies which is listed in Indonesia Stock Exchange over the four year period 2012-2014. Sample in this research are selected by purposive sampling and the data was analyzed using multiple linear regression. Only 96 companies meet the criteria. The results of the research showed that profitability, previous year’s dividend and free cash flow have influence to cumulative dividend policy. Firm maturity, investment opportunities, leverage, firm size, liquidity have no influence to dividend policy.